2013
DOI: 10.1002/cncr.28422
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic outcomes of patients with brain metastases based on symptoms: An argument for routine brain screening of those treated with upfront radiosurgery

Abstract: BACKGROUND:Insurers have started to deny reimbursement for routine brain surveillance with magnetic resonance imaging (MRI) after stereotactic radiosurgery (SRS) for brain metastases in favor of symptom-prompted imaging. The authors investigated the clinical and economic impact of symptomatic versus asymptomatic metastases and related these findings to the use of routine brain surveillance. METHODS: Between January 2000 and December 2010, 442 patients underwent upfront SRS for brain metastases. In total, 127 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 21 publications
(43 reference statements)
0
49
0
Order By: Relevance
“…Other factors including local failure risk, life expectancy, leptomeningeal involvement, current cognitive function and practitioner bias contribute to this decision. Despite these other factors, DBF is an endpoint that significantly affects the cost of future care as it can lead to multiple salvage treatments given its prevalence and the cost of multiple SRS procedures [1, 2]. The use of salvage WBRT after SRS ranged from 5 to 20% amongst the SRS centers in the current study, suggesting that the standards for use of WBRT vary amongst institutions.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other factors including local failure risk, life expectancy, leptomeningeal involvement, current cognitive function and practitioner bias contribute to this decision. Despite these other factors, DBF is an endpoint that significantly affects the cost of future care as it can lead to multiple salvage treatments given its prevalence and the cost of multiple SRS procedures [1, 2]. The use of salvage WBRT after SRS ranged from 5 to 20% amongst the SRS centers in the current study, suggesting that the standards for use of WBRT vary amongst institutions.…”
Section: Discussionmentioning
confidence: 92%
“…SRS is approximately four-fold more expensive than whole brain radiotherapy (WBRT) but has been proven to be more cost-effective in selected patient populations [2, 3]. While the use of upfront WBRT may mitigate the likelihood of DBF [4], it is associated with toxicities such as fatigue [5] and cognitive decline [6].…”
Section: Introductionmentioning
confidence: 99%
“…Post-contrast MRI was capable of detecting asymptomatic metastatic brain lesions that were missed on contrast-enhanced CT in lung cancer patients, and can be regarded as superior to contrast-enhanced CT in diagnosing occult brain metastases [12,13,14]. Yokoi et al [33] reported median survival times of 10 months for CT-detected brain metastases and 17 months for MRI-detected brain metastases. Patients who presented with symptomatic brain metastases had worse clinical outcomes as compared to those without symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This improvement has been due to a combination of improved systemic therapies 18,19 , improved brain-directed therapies 20 , and earlier detection of metastases 21 . It is unclear, however, whether geriatric oncology patients face a bias with regards to the use of aggressive treatment for brain metastases.…”
Section: Discussionmentioning
confidence: 99%